Comparison of insulin degludec with insulin glargine in insulin‐naive subjects with Type 2 diabetes: a 2‐year randomized, treat‐to‐target trial. Issue 11 (30th September 2013) - Rodbard, H. W.; Cariou, B.; Zinman, B.; Handelsman, Y.; Philis‐Tsimikas, A.; Skjøth, T. V.; Rana, A.; Mathieu, C.
Abstract Aims The aim of this study was to compare long‐term safety and efficacy of the basal insulin analogue degludec with glargine in insulin‐naive subjects with Type 2 diabetes. Methods This open‐label trial included a 52‐week core period followed by a 52‐week extension. Participants were randomized 3:1 to once‐daily degludec or glargine, administered with metformin ± dipeptidyl peptidase‐4 inhibitors. Basal insulin was titrated to target pre‐breakfast plasma glucose 3.9–4.9 mmol/l. Results At end of treatment (104 weeks), mean HbA1c reductions were similar for degludec and glargine; estimated treatment difference between degludec and glargine was 1 mmol/mol (95% CI −1 to 3) [0.07% (95% CI −0.07 to 0.22)], P = 0.339 in the extension trial set (degludec 551, glargine 174), comprising subjects who completed core trial and continued into the extension trial. Overall confirmed hypoglycaemia rates (1.72 vs. 2.05 episodes/patient‐year), rates of adverse events possibly or probably related to trial product (0.19 events/patient‐year), weight gain (2.7 vs. 2.4 kg) and mean daily insulin doses (0.63 U/kg) were similar between treatments in the safety analysis set (degludec 766, glargine 257) comprising all treated subjects. Rates of nocturnal confirmed hypoglycaemia (0.27 vs. 0.46 episodes/patient‐year; P = 0.002) and severe hypoglycaemia (0.006 vs. 0.021 episodes/patient‐year, P = 0.023) were significantly lower with degludec for the safety analysis set (analysis based on intention‐to‐treat full analysis set comprising all randomized subjects). Conclusions In Type 2 diabetes, insulin degludec in combination with oral anti‐diabetic drugs, safely and effectively improves long‐term glycaemic control, with a significantly lower risk of nocturnal hypoglycaemia as compared with glargine.